Learning Ability as a Function of Practice: Does It Apply to Farmworkers?. Issue 6 (June 2015) - Nguyen, Ha T.; Quandt, Sara A.; Summers, Phillip; Morgan, Timothy M.; Chen, Haiying; Walker, Francis O.; Howard, Timothy D.; Galván, Leonardo; Arcury, Thomas A.
Abstract : Objective: Farmworkers experience significant work-related health risks including pesticide-associated cognitive impairment. Practice effect is a surrogate for learning ability. This study examined differences in cognitive function and learning capacity in Latino farmworkers and nonfarmworkers. Methods: Tasks of learning and short-term memory, executive function and working memory, perceptual coding, and psychomotor function were assessed at baseline and 3-month follow-up in 136 farmworkers and 116 nonfarmworkers. Results: Farmworkers had better performance on visuospatial learning and short-term memory at baseline ( P < 0.05). Nevertheless, nonfarmworkers showed more practice effects, or improvement on cognitive performance, at 3-month follow-up relative to farmworkers. Furthermore, the amount of improvement on visuospatial learning ability, short-term visuospatial memory, and perceptual coding ability was significantly higher in nonfarmworkers than in farmworkers. Conclusions: Practice effects may serve as an additional cognitive readout to differentiate healthy individuals from those with cognitive impairment.